Lipid alternations in the plasma of COVID-19 patients with various clinical presentations - Liang, Xiao; Qi, Xin; Yang, Jin; Wang, Xiaorui; Qin, Hongyu; Hu, Fang; Bai, Han; Li, Yixin; Zhang, Chengsheng; Shi, Bingyin (Frontiers in Immunology, 2023)
COVID-19 is a highly infectious respiratory disease that can manifest in various clinical presentations. Although many studies have reported the lipidomic signature of COVID-19, the molecular changes in asymptomatic severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infected individuals remain elusive.This study combined a comprehensive lipidomic analysis of 220 plasma samples from 166 subjects, including 62 healthy controls, 16 asymptomatic infections, and 88 COVID-19 patients. We quantified 732 lipids separately in this cohort. We performed difference analysis, validated with machine learning models, and also performed GO, KEGG pathway enrichment analysis using differential lipids from different control groups.We found 175 differentially expressed lipids associated with SASR-CoV-2 infection, disease severity, and viral persistence in patients with COVID-19. PC (O-20:1/20:1), PC (O-20:1/20:0), and PC (O-18:0/18:1) better distinguished asymptomatic infected individuals from normal individuals. Furthermore, some patients tested positive for SARS-CoV-2 nucleic acid by RT-PCR but did not become negative for a longer period of time (≥60 days, designated here as long-term nucleic acid test positive, LTNP), whereas other patients became negative for viral nucleic acid in a shorter period of time (≤45 days, designated as short-term nucleic acid test positive, STNP). We have found that TG (14:1/14:1/18:2) and FFA (4:0) were differentially expressed in LTNP and STNP.In summary, integration of lipid information can help us discover novel biomarkers to identify asymptomatic individuals and further deepened our understanding of the molecular pathogenesis of COVID-19.